THE PROCESS OF FORMING AN ANTI-VIOLENCE CULTURE AMONG GENERATION Z STUDENTS THROUGH PROJECT-BASED LEARNING WITH THE REINFORCEMENT OF SOCIAL-EMOTIONAL LEARNING - Hikmah Wifaqi; Nur Ali (SOSIOEDUKASI, 2026)
Violence in schools remains a serious problem, so participation in education is expected to minimize the violence that occurs. This study aims to describe the process of internalizing anti-violence values in Social Studies learning through Project Based Learning (PjBL) and strengthening Social Emotional Learning (SEL) as an effort to form an anti-violence culture among Gen Z students in grade VIII at Al-Hikmah International Islamic Boarding School (IIBS) Batu. The approach used is qualitative with a case study, involving social studies teachers as the main informants, eighth-grade students as the recipients of social conflict material, and the school as supporting informants. Data collection was conducted through interviews, observations, and documentation, then analyzed using the Miles et al. model, which includes condensation, presentation, and data verification. The results showed that the process of internalizing anti-violence values occurred in three stages. The first stage was the design of an anti-violence culture through the preparation of lesson plans by social studies teachers on social conflict material. The second stage is the implementation of the design through the Project Based Learning (PjBL) approach and the strengthening of Social Emotional Learning (SEL) during the learning process. Finally, the target achievement of the design is through cognitive, affective, and psychomotor based evaluation. These three stages reflect the formation of tolerant, empathetic student behavior and the ability to resolve conflicts peacefully, thereby reflecting the formation of an anti-violence culture through social studies learning that is in line with SDG 16.1 regarding the reduction of violence.